Diversidade patogênica em isolados de Thielaviopsis paradoxa provenientes de diferentes áreas produtoras de cana-de-açúcar - Sansoli Chanquinie, Débora Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Thielaviopsis paradoxa, causal agent of pineapple disease is a main cause of poor germination of sugarcane sets. The disease is one of major cause for the reduction of budding and consequent failures on the stand. There is no resistant varieties, and as faster is the plant emergence, less is the damage caused by the pathogen. In this study it was evaluated the pathogenic diversity of eleven isolates of T. paradoxa from stalks of sugarcane with symptoms collected from five Brazilian states (SP, GO, MG, BA and PR). For the inoculation it was used sugarcane sets of the variety IACSP95-5000, with nine months of age. Data analysis revealed differences among the isolates, especially isolates 6 and 7, the most pathogenic, both from Guaíra-SP. The isolated 2, from Santa Juliana-MG was the least pathogenic. Additional tests with three contrasting isolates (low, intermediate and high level of pathogenicity) inoculated in three varieties of sugarcane (IACSP95-5000, IAC911099 and IACSP97-4039) confirmed the different behavior, being reproduced phenotypic characteristics similar to those when inoculated in variety IACSP955000 . The three varieties of sugarcane used in this study showed to be susceptibles, with indication and possible evidence of absence of resistant varieties. It was not found relation between the geographical origin of the isolates and pathogenicity levels. In vitro tests with fungicides of the strobilurin group (pyraclostrobin and trifloxystrobin) and triazole (tebuconazole) at concentrations of 1, 10 and 100μgmL-1 active ingredient, became clear that only the fungicide tebuconazole alone or in combination with trifloxystrobin, showed efficient in inhibiting the size of the colonies, when at 100μgmL-1. Complementary studies about the fungicide viability of the group triazoles, in vitro, at higher ...

Thielaviopsis paradoxa, agente causal da podridão-abacaxi, é um fungo apontado como a principal causa da baixa germinação de toletes de cana-de-açúcar. A doença é uma das principais causas pela redução da brotação e consequente falhas no stand. Não existem variedades resistentes, e quanto mais rápida é a emergência das plantas, menor é o dano causado pelo patógeno. Nesse estudo foi avaliada a diversidade patogênica de onze isolados de T. paradoxa oriundos de toletes de canas-de-açúcar com sintomas, coletados em cinco Estados brasileiros (SP, GO, MG, BA e PR). Na inoculação foram empregados toletes de cana-de-açúcar da variedade IACSP95-5000, de nove meses de idade. Constatou-se diferença estatisticamente significativa entre os isolados, com destaque para os isolados 6 e 7, os mais patogênicos, ambos provenientes de Guaíra-SP. O isolado 2, proveniente de Santa Juliana-MG, foi o menos patogênico. Testes complementares com três isolados contrastantes (baixo, intermediário e alto grau de patogenicidade) inoculados em três variedades de cana-de-açúcar (IACSP95-5000, IAC911099 e IACSP97-4039) comprovaram o comportamento diferenciado, sendo reproduzidas características fenotípicas semelhantes àquelas quando da inoculação na variedade IACSP95-5000. As três variedades de cana-de-açúcar empregadas nesse estudo mostraram-se suscetíveis, com indicação e possível comprovação da inexistência de variedades resistentes. Não foi constatado relação entre a origem geográfica dos isolados e níveis de patogenicidade. Testes in vitro com fungicidas dos grupos das estrobilurinas (trifloxistrobina e piraclostrobina) e triazol (tebuconazole), nas concentrações 1, 10 e 100 μgmL-1 de ingrediente ativo, tornaram evidente que apenas o fungicida tebuconazole, isoladamente ou em combinação com trifloxistrobina, mostrou-se eficiente na inibição do tamanho das colônias...
Keywords: Cana-de-açúcar - Doenças e pragas; Fungos fitopatogenicos; Pragas agricolas; Diversidade genética; Fungicidas; Fungi in agriculture